Facing a blind alley - Experiences of stress-related exhaustion: a qualitative study - Lilas Ali; Andreas Fors; Inger Ekman; Sara Alsén (BMJ Open)
Introduction Mental illness is a major concern in many countries. In Sweden, stress-related mental illness is currently the most frequent reason for sick leave.Objective This study aimed to explore patients’ experiences of stress-related exhaustion.Design A qualitative study with interview data analysed using a phenomenological hermeneutic method.Setting Participants were selected from public primary healthcare centres in a larger city in western Sweden.Participants Seven women and five men on sick leave from work due to stress-related exhaustion were included in the study.Findings Stress-related exhaustion was experienced as a loss of access to oneself and one’s context and feelings of being trapped and lost in life. The condition had a significant impact on personal identity, raised existential issues and was interpreted as facing a blind alley. Participants described a mistaken direction in life, being forced to stop, change direction and act differently.Conclusion Stress-related exhaustion is a challenging, life-changing existential experience that involves a crisis with an opportunity for new insights. Careful consideration of patients’ narratives together with the expertise of healthcare professionals can be combined to improve health and optimise recovery based on individual’s situation.